Shapes of freedom Hegel's philosophy of world history in theological perspective - Hodgson, Peter Crafts, 1934- (Oxford : Oxford University Press, 2012)
Hodgson explores Hegel's vision of history as the progress of the consciousness of freedom. Freedom is not simply a human production, but takes shape through the interweaving of the divine idea and human passions, and such freedom defines the purpose of historical events in the midst of apparent chaos. Interpretations of freedom are examined in the context of present-day questions about what they mean and whether they still have validity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Liberty; Liberty -- Religious aspects; History -- Philosophy